2016
DOI: 10.4315/0362-028x.jfp-16-085
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy Knowledge and Attitudes of Restaurant Managers and Staff: An EHS-Net Study

Abstract: Dining outside of the home can be difficult for persons with food allergies who must rely on restaurant staff to properly prepare allergen-free meals. The purpose of this study was to understand and identify factors associated with food allergy knowledge and attitudes among restaurant managers, food workers, and servers. This study was conducted by the Environmental Health Specialists Network (EHS-Net), a collaborative forum of federal, state, and local environmental health specialists working to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 9 publications
11
62
2
Order By: Relevance
“…These data can contribute to generating hypotheses about the context in which outbreaks occur. For example, the proportion of establishments with outbreaks engaging in complex food preparation processes (87%) is high compared with the proportion of establishments without outbreaks engaging in these processes (approximately 50%) found in other studies (EHS-Net restaurant cooling practices study, unpublished data, CDC, 2009) ( 20 ). This difference suggests that outbreaks might occur more often in establishments where complex food preparation occurs.…”
Section: Discussionmentioning
confidence: 77%
“…These data can contribute to generating hypotheses about the context in which outbreaks occur. For example, the proportion of establishments with outbreaks engaging in complex food preparation processes (87%) is high compared with the proportion of establishments without outbreaks engaging in these processes (approximately 50%) found in other studies (EHS-Net restaurant cooling practices study, unpublished data, CDC, 2009) ( 20 ). This difference suggests that outbreaks might occur more often in establishments where complex food preparation occurs.…”
Section: Discussionmentioning
confidence: 77%
“…Overall the managers, food workers, and servers were knowledgeable about food allergens and had positive attitudes about accommodating those with food allergies; however, it was noted that 10% of workers thought a person with a food allergy could safely consume a small amount of the allergen. The study also showed that allergy training improved attitudes towards the patients with food allergies but not the knowledge [50]. For patient safety, discussing eating out as well as tactics on how to do it successfully are essential.…”
Section: Eating Outmentioning
confidence: 90%
“…Among the 1,307 restaurants contacted for participation in the study, 852 met the study eligibility criteria, and 278 (32.6%) of those agreed to participate; 58 restaurants were excluded because they did not have an English-speaking manager, and another 177 were excluded because they did not meet the restaurant definition for EHS-Net inclusion. Data on restaurant, manager, food worker, and server characteristics have been published previously ( 4 ). Among 277 managers, 123 (44.4%) reported that they had received training on food allergies while working at their respective restaurants ( Table 1 ).…”
mentioning
confidence: 99%